Management of Education Personnel in Improving Administrative Performance in the 4.0 Era - Alfiyani, Nurul; Supriatman, Maman; Masduki, Masduki (Educational Insights, 2023)
Management of education personnel aims to utilize education personnel effectively and efficiently to achieve optimal results. The purpose of this research is to find out how to improve the performance of the administrative sector in the 4.0 era. The method used is a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation. The data analysis process is carried out with the stages of data collection, data reduction, data presentation and drawing conclusions. Based on this research the management of education personnel in improving the performance of the administrative field in the 4.0 era, namely planning to improve the performance of the administrative field by placing employees with existing employees in order to be able to improve work performance, Implementation in improving the performance of the administrative sector by training and providing compensation, evaluation in the development of education personnel is needed to develop skills, knowledge and attitudes, and evaluating the dismissal of education personnel by balancing the needs of employees with the goals of the school.